Preparation and characterization of pH-sensitive hydrogels from photo-crosslinked poly(ethylene glycol) diacrylate incorporating titanium dioxide - Senol, Sebnem; Akyol, Emel (SCIENDO, 2020)
The purpose of the present investigation was to prepare pH-sensitive hydrogels from photo-crosslinked poly(ethylene glycol) diacrylate (PEG-DA). Rutile titanium dioxide (TiO2) was employed to modify the PEG-DA hydrogels. The rutile titanium dioxide (TiO2) nanoparticles were prepared by direct oxidation of titanium in the presence of polyethylene glycol (PEG) at high temperature. The nanoparticles were characterized by FT-IR, XRD and SEM. The influence of experimental conditions, such as pH, type and amount of photoinitiators on the release profiles of donepezil hydrochloride (active pharmaceutical ingredient for Alzheimer disease) from modified PEG-DA hydrogels, was investigated. The drug release processes were analyzed kinetically using zero-order, first-order, Hixson-Crowell and Peppas models.
Keywords: PEG-DA based hydrogels; rutile titanium oxide; release profiles; kinetic models; CONTROLLED-RELEASE; DRUG-DELIVERY; PHOTOPOLYMERIZATION; TIO2; DONEPEZIL; HYDROXYAPATITE; NANOPARTICLES; Materials Science